Terrorism and the Rule of Law - Leila Nadya Sadat (Washington University Global Studies Law Review, 2004)
It is the premise of this Essay that by characterizing the September 11th attacks as acts of war rather than as terrorism or crimes against humanity, the United States has lost what could have been an extraordinary opportunity to strengthen international legal norms and combat international terrorism.
Keywords: Crimes against humanity; Declaration of war; International law; Terrorism; United States foreign relations; World Trade Center and Pentagon Attacks; 2001; International; United States